Disguising ethnic domination as accommodation or integration - John McGarry (Frontiers in Political Science)
This article examines how and why regimes that dominate particular ethnic communities on behalf of a dominant one disguise themselves by claiming to practice accommodation (consociational power-sharing and territorial autonomy) or integration (equal citizenship with respect for private cultural differences). It also explains how to distinguish authentic accommodation and integration from the sham forms used by these regimes. The article seeks to help identify domination regimes that would otherwise be overlooked. This is important for academics. It is also important for international policymakers who seek to condemn domination and make it more difficult to maintain.